The Effectiveness of Developing Canva Web-Based Interactive Learning Media In Increasing Students’ Interest in Learning History - Ilham, Muhammad; Dedy Miswar, Dedy Miswar; Sugeng Widodo, Sugeng Widodo; Yunisca Nurmalisa, Yunisca Nurmalisa (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to analyse the effectiveness of developing Canva-based interactive web learning media in improving learning outcomes in History. The background of this study stems from the challenges of history learning, which has been considered monotonous, lacking in interactivity, and focused on memorisation, resulting in low student engagement and motivation. The development of Canva-based interactive media is expected to provide a more engaging, visual, and interactive learning experience through the integration of text, images, animations, audio, and automatic evaluation features in a single platform. The research approach used is a mixed method with a quasi-experimental design and media feasibility testing through expert validation, student response questionnaires, and learning outcome analysis through pre-tests and post-tests. The results of the study indicate that Canva-based learning media has a very good level of feasibility based on the assessments of media experts and subject matter experts. In addition, there was a significant increase in learning outcomes after using the media, as demonstrated by statistical tests and comparisons of scores before and after treatment. Students showed positive responses, particularly in terms of interest, ease of understanding the material, and increased motivation to learn. Thus, Canva-based interactive learning media is considered effective as an innovation in history learning in the digital age and is suitable for wider implementation in the context of 21st-century education.